Relationship between sphenoid sinus volume and accessory septations: A 3D assessment of risky anatomical variants for endoscopic surgery. Issue 5 (2nd October 2019) - Gibelli, Daniele; Cellina, Michaela; Gibelli, Stefano; Cappella, Annalisa; Oliva, Antonio Giancarlo; Termine, Giovanni; Sforza, Chiarella
ABSTRACT: Sphenoid sinus accessory septations involve serious complications during their removal for the injury of the internal carotid artery (ICA) and the optic nerve (ON). The relationships of this anatomical variant with sphenoid size still remain unclear. In the present study, 260 patients (equally divided among sexes, aged between 18 and 92 years) were retrospectively assessed. Number of accessory septations and their relationship with ICA and ON were recorded. The 3D model of sphenoid sinuses was extracted. Pearson's coefficient was calculated to assess correlations between the volume of sphenoid sinuses and the number of septations ( P  < 0.05). Sex‐related differences in prevalence of septations inserted onto ICA or ON were assessed through chi‐square test ( P  < 0.05). Differences in volume between patients with and without ICA or ON septal insertions were assessed through Mann–Whitney test ( P  < 0.05). In most of the cases, two septations were found (24.6%), whereas only 21.9% of patients did not show any septum. ICA and ON septal insertions were found in 20.8% and 7.7% of cases, respectively. Number of septations significantly increased with sinus volume, independently from sex ( P  < 0.001). Moreover, volume was significantly higher in patients with ICA septal insertion ( P  < 0.001), whereas no difference was found between subjects with and without ON septal insertion ( P > 0.05). The present study first proved that septations and probability of ICA insertion are related with sphenoid volume. On the other side, ON insertion does not depend upon sphenoid sinuses size. Anat Rec, 303:1300–1304, 2020. © 2019 American Association for Anatomy